PENGUATAN PENGUASAAN TENSES MELALUI MEDIA INTERAKTIF BOARD GAME - Rangkuti, Linda Astuti; Fransiska, Widia; Zulkarnain, Iskandar; Sihite, Meida Rabia; Nasution, Putra Thoip (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2024)
Mastering tenses is a fundamental aspect of learning English; however, it remains a challenge for many learners. This Community Service Program that was conducted in the ninth-grade at SMA Muhammadiyah 1 aims to enhance the understanding and application of tenses through the use of an interactive board game. The method employed is a game-based learning approach, where participants actively engage in activities that encourage contextual comprehension of tenses. The program involves students as the primary participants and is conducted in several stages, including socialization, training, implementation, and evaluation. The results indicate that using a board game not only significantly improves students' understanding of tenses but also increases their motivation and engagement in learning. Thus, this method can serve as an effective alternative for teaching tenses in both formal and non-formal educational settings. Keywords: Tenses, Interactive Media, Board Game, English Learning